2013
DOI: 10.1186/1471-2458-13-744
|View full text |Cite
|
Sign up to set email alerts
|

Stores Healthy Options Project in Remote Indigenous Communities (SHOP@RIC): a protocol of a randomised trial promoting healthy food and beverage purchases through price discounts and in-store nutrition education

Abstract: BackgroundIndigenous Australians suffer a disproportionate burden of preventable chronic disease compared to their non-Indigenous counterparts – much of it diet-related. Increasing fruit and vegetable intakes and reducing sugar-sweetened soft-drink consumption can reduce the risk of preventable chronic disease. There is evidence from some general population studies that subsidising healthier foods can modify dietary behaviour. There is little such evidence relating specifically to socio-economically disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…With the increasing availability and affordability of healthy food options in local community stores a randomized controlled trial is currently being implemented to determine if a reduction in healthy food prices influences dietary behaviour changes. [27] Health practitioners' knowledge of follow-up procedures varied ranging from fair to excellent. The introduction of electronic health records over the last 10 years has greatly improved the generation of recall lists to follow-up participants that have been flagged for review.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability and affordability of healthy food options in local community stores a randomized controlled trial is currently being implemented to determine if a reduction in healthy food prices influences dietary behaviour changes. [27] Health practitioners' knowledge of follow-up procedures varied ranging from fair to excellent. The introduction of electronic health records over the last 10 years has greatly improved the generation of recall lists to follow-up participants that have been flagged for review.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47] Nevertheless, they address some important research gaps regarding consumer behaviour. Elbel et al 48 tested the potential of 5 different taxation (at 30%) and labeling conditions among a high-need population to induce consumers to purchase healthier foods and beverages.…”
mentioning
confidence: 97%
“…directly collected checkout scanner data, commercially available data sets and grocery receipts) have been used to monitor the effectiveness of interventions in a variety of types of retail food stores, [9][10][11][12] including a number of recent small-store studies. [13][14][15][16][17] Together, these studies suggest that sales data can actually be used in the design of retail food interventions. For example, Foster and colleagues 9 found that low-cost strategies focussed on improving product availability and placement enhanced sales of some foods and beverage categories (milk, water, frozen meals) but not others (regular soda, diet soda, cereal).…”
Section: Introductionmentioning
confidence: 99%